The influence of the holistic vision in the hospital humanization - Alves de Almeida Fernandes Leite, Telma; Strong, Maria Isabel (O Mundo da Saúde, 2006)
This work aimed to reflect on the influence of employing the holistic vision in hospital assistance humanization process. The applied methodology was a bibliographical survey on the subject, both regarding hospital humanization in its relation to the holistic paradigm and assumptions coming from other knowledge areas. Historically, health practices began with an integrated view of human beings in their environment. One perceives that the dehumanization process resulted from multiple factors, figuring among them exact sciences effort to explain objectively human beings removing from them all subjective aspects, commodifying them; because of techno- logy veneration, mechanizing them; and by excessive specialization, fragmenting them. Hospital Institutions are increasingly suffering economic and cultural influences and this generates several changes that must have evaluated their intrinsic potential to affect the quality of assistance and the relation between health professionals and users. The health concept, the formation of the professional and human resources management in hospitals can also influence assistance quality. The holistic vision favors the humanization process, influencing the professionals, the users and the relationships between them.